Migrating industrial relations: migrant workers’ initiative within and outside trade unions - Alberti, Gabriella; Però, Davide (Wiley, 2018)
This article develops an embedded actor‐centred framework for studying the mobilization and bargaining practices of migrant workers. This framework is applied to examine two instances of labour organizing by low‐paid Latin American workers in London showing how migrant workers can develop innovative collective initiatives located at the junction of class and ethnicity that can be effective and rewarding in material and non‐material terms. In particular, the article shows that while there is a growing interest on the part of established unions to represent migrant workers, their bargaining and mobilization strategies appear inadequate to accommodate the bottom‐up initiatives of such workers who, as a result, have started to articulate them independently. On the basis of the findings obtained, we thus argue in favour of an actor‐centred framework to the study of migration and IR to better identify migrant workers’ interests, identities and practices as shaped by complex regulatory and social context.